Risk Factors Associated with Nutritional Status of Toddlers - Ria Wati; Isti Istianah (Sarana Ilmu Indonesia (salnesia), 2023)
The main nutritional problem is when growing children experience severe malnutrition. Such as the mother's education level, occupation, number of family members, family income, knowledge, history of exclusive breastfeeding, and history of infectious diseases are several variables that influence a child's nutritional status. Body weight for age (WW/U) based on Z-score -3 SD to <-2 SD is the threshold for undernutrition. The aim of this research was to determine the factors related to the nutritional status of toddlers in the UPTD work area of the Kubangdeleg Community Health Center, Cirebon Regency, West Java Province. This research uses a cross sectional study design and is an observational analytical study. The sample size of 100 people is mothers who have toddlers aged 12-59 months. Data collection was carried out through interviews and anthropometric measurements as well as community health center reports. Then the data was analyzed univariate and bivariate with the Chi-square test. Maternal education obtained (p-value=0,027), number of family members (p-value=0,317), maternal knowledge about nutrition (p-value=0,756), history of exclusive breastfeeding (p-value=1,000), and history of infectious diseases (p-value=0,693). There is a relationship between the level of maternal education and the nutritional status of toddlers. Meanwhile, in the UPTD work area of the Kubangdeleg Community Health Center, Cirebon Regency, West Java Province. Several factors including the number of family members, mother's knowledge, history of exclusive breastfeeding and history of infectious diseases are not risk factors for nutritional status in toddlers.